Performance and Application of Spraying Acrylic Emulsion Cement Paste on Concrete Surface of Water Conveyance Tunnel - CUI Dehao; TANG Jianhui; ZHANG Wei; TIAN Jialin; BAI Yin (Renmin Zhujiang)
In order to explore the applicability of acrylic emulsion cement paste in concrete surface protection of water conveyance structures,the fluidity,tensile strength,compressive strength,and flexural strength of acrylic emulsion cement paste were analyzed by taking aggregate-cement ratio and emulsion concentration as variable factors,and the operable time of acrylic emulsion cement paste was analyzed by interlaminar bonding strength test.Finally,the ratio of acrylic emulsion cement paste for spraying construction was obtained.The results show that the fluidity of acrylic emulsion cement paste decreases with the decrease in aggregate-ash ratio and increases first and then decreases with the decrease in emulsion concentration.With the decrease in emulsion concentration,the compressive strength of acrylic emulsion cement paste increases,while the tensile strength and anti-sticking strength decrease.Through the ratio of compressive strength to tensile strength,it is found that the increase in emulsion concentration can increase the toughness of acrylic emulsion cement paste.The interlaminar bond strength of acrylic emulsion cement paste decreases with the extension of the pouring time interval,so it is recommended that the construction interval should not exceed 1 h.The practical application shows that the concrete matrix can be strengthened,and the high bonding strength can be formed by using acrylic emulsion cement paste for tunnel surface protection,which can provide a reference for similar concrete surface protection.